2021
DOI: 10.3390/biomedicines9081062
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Lipidomics of Mitochondria in a Cellular Alzheimer’s Disease Model

Abstract: Alzheimer’s disease (AD) is neuropathologically characterized by the accumulation of Amyloid-β (Aβ) in senile plaques derived from amyloidogenic processing of a precursor protein (APP). Recently, changes in mitochondrial function have become in the focus of the disease. Whereas a link between AD and lipid-homeostasis exists, little is known about potential alterations in the lipid composition of mitochondria. Here, we investigate potential changes in the main mitochondrial phospholipid classes phosphatidylchol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 88 publications
0
17
0
Order By: Relevance
“…Nevertheless, PG is a precursor of cardiolipin (which content and FA composition have been confirmed to be altered in AD [ 44 ]), so it is understandable that these changes could be caused by alterations in the PG profile. A recent study has also shown that some PG species (18:2/16:0, 18:2/16:1, 18:2/18:1, 18:2/18:2, 18:2/20:3, and 18:2/20:4) with FAs mainly found in cardiolipin are increased in a cellular AD model in comparison to a control cell [ 11 ]. Based on those studies, our results suggest that the decrease of some PGs together with the increase of PUFAs could be related with the neuroprotective potential of the DS extract against the different AD toxic agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, PG is a precursor of cardiolipin (which content and FA composition have been confirmed to be altered in AD [ 44 ]), so it is understandable that these changes could be caused by alterations in the PG profile. A recent study has also shown that some PG species (18:2/16:0, 18:2/16:1, 18:2/18:1, 18:2/18:2, 18:2/20:3, and 18:2/20:4) with FAs mainly found in cardiolipin are increased in a cellular AD model in comparison to a control cell [ 11 ]. Based on those studies, our results suggest that the decrease of some PGs together with the increase of PUFAs could be related with the neuroprotective potential of the DS extract against the different AD toxic agents.…”
Section: Discussionmentioning
confidence: 99%
“…SH-SY5Y cells present a mature neuron-like phenotype when differentiated with retinoic acid (RA) and brain-derived neurotrophic factor (BDNF), simulating the early-stage pathophysiology of cholinergic neurons affected by AD [9]. Previous works have analyzed the lipidomic composition of this cell line [10] and, more recently, the potential changes in mitochondrial phospholipid classes of SH-SY5Y transfected cells to simulate an AD model [11]. Moreover, the effect of an olive extract on these cells has also been evaluated in terms of lipid alterations [12].…”
Section: Introductionmentioning
confidence: 99%
“…Among the different in vitro models used to study AD, the SH-SY5Y cell line has been widely used as a first step for investigating and assessing the neuroprotective effects of natural compounds because of their possible differentiation into neuron-like cells ( 17 , 43 ). The in vitro toxicity results obtained in this study indicate that 20 and 40 μg/mL concentrations of OL-SS did not alter the cell viability of differentiated SH-SY5Y in comparison to control cells after 24 h, so the highest concentration (40 μg/mL) was selected to pre-treat the cells before the addition of 30 μM of the neurotoxic agent Aβ1–42 [the concentration used was based on previous studies ( 19 , 44 )]. As a result, the pre-treatment with OL-SS before the addition of Aβ1–42 for another 24 h was able to attenuate cell death caused by Aβ1–42.…”
Section: Discussionmentioning
confidence: 99%
“…This cell line is of human origin, catecholaminergic, easy to maintain, and reported to be differentiable into a more mature neuron-like phenotype ( 16 , 17 ). The global lipid analysis of this cell has been determined in a previous work ( 18 ), as well as the potential changes in the main mitochondrial phospholipid classes in a cellular AD-model ( 19 ). This cell line has been also used to evaluate the neuroprotective potential of different compounds, such as olive biophenols ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prior to mass spectrometry analysis, lipids from a 100 µg sample were extracted using the solid/liquid lipid extraction method as described earlier in detail [ 43 , 44 , 45 ]. Afterward, shotgun lipidomics was performed on a 4000-quadrupole linear-ion trap (QTrap,) equipped with a Turbo Spray ion source from AB Sciex (Darmstadt, Germany) and couplet to an autosampler of the Agilent HPLC 1200 series (Santa Clara, CA, USA).…”
Section: Methodsmentioning
confidence: 99%